Colchicine for postoperative pericardial effusion: a multicentre, double-blind, randomised controlled trial. Issue 21 (15th June 2015) - Meurin, P; Lelay-Kubas, S; Pierre, B; Pereira, H; Pavy, B; Iliou, M C; Bussière, J L; Weber, H; Beugin, J P; Farrokhi, T; Bellemain-Appaix, A; Briota, L; et al.
Abstract : Objectives: Pericardial effusion is common after cardiac surgery. Growing evidence suggests that colchicine may be useful for acute pericarditis, but its efficacy in reducing pericardial effusion volume postoperatively has not been assessed. Methods: This randomised, double-blind, placebo-controlled study conducted in 10 centres in France included 197 patients at high risk of tamponade (ie, with moderate to large-sized persistent effusion (echocardiography grades 2, 3 or 4 on a scale of 0–4)) at 7–30 days after cardiac surgery. Patients were randomly assigned to receive colchicine, 1 mg daily (n=98), or a matching placebo (n=99). The main end point was change in pericardial effusion grade after 14-day treatment. Secondary end points included frequency of late cardiac tamponade. Results: The placebo and the colchicine groups showed a similar mean baseline pericardial effusion grade (2.9±0.8 vs 3.0±0.8) and similar mean decrease from baseline after treatment (−1.1±1.3 vs −1.3±1.3 grades). The mean difference in grade decrease between groups was −0.19 (95% CI −0.55 to 0.16, p=0.23). In total, 13 cases of cardiac tamponade occurred during the 14-day treatment (7 and 6 in the placebo and colchicine groups, respectively; p=0.80). At 6-month follow-up, all patients were alive and had undergone a total of 22 (11%) drainages: 14 in the placebo group and 8 in the colchicine group (p=0.20). Conclusions: In patients with pericardial effusion after cardiac surgery, colchicine administration does not reduce the effusion volume or prevent late cardiac tamponade. Clinical trial reg No: NCT01266694.